Safety Performance Functions for Mountain Two-lane Rural Roads in Ecuador - García-Ramírez, Yasmany (Ingeniería, 2024)
The two-lane rural road on mountainous roads has various design and operational challenges. This complexity could produce a road with specific geometric configurations or segments where the probability of a road accident increases. The Highway Safety Manual (HSM) offers a predictive model to detect such sites using Safety Performance Functions (SPF). These functions predict the number of road crashes at the different roadway elements and apply to all project phases. Many functions or equations have been developed worldwide; however, in Ecuador, they have not yet been estimated. Therefore, this study aims to propose Safety Performance Functions for two-lane rural roads in Ecuador in mountainous environments. To do this, design and operation variables were collected from 25 roads in the Ecuadorian Andes. The SPFs were developed with crash data from 2017-2019 and validated with information from 2020-2021. As a result, 12 SPFs were developed for three types of crashes (total, fatal + injury, property damage only) and various ranges of annual average daily traffic (AADT). These equations estimate the average expected frequency of accidents for existing conditions, alternatives for existing conditions, or proposed new road projects. This study will improve the road safety of the built roads and new projects.